A Passive Decoupling Mechanism for Misalignment Compensation in Master-Slave Teleoperation - Shen Treratanakulchai (2022)
Teleoperated robots are commonly used in minimally invasive surgery as they can control surgical instruments at a distance. An operator sends the motion command via a master console, which must convert these into suitable slave instrument actuator inputs for intuitive interaction. However, most master-slave systems available to date use incremental task-space control and clutching, which introduces a discontinuity and orientation misalignment between the master control handle and slave instrument, with a consequent impact on task performance. In this article, we proposed a new master manipulator design to compensate for misalignment mechanically. The modular gimbal consists of a passive decoupling mechanism and a wrist locking feature. After describing the mechanisms and its kinematic configuration, we report on a comparative study under controlled conditions, developed to measure the end effector orientation in both compensated and non-compensated scenarios. The results demonstrate that the compensated master console maintains a near constant end effector orientation over the workspace during clutching, showing great promise as a solution to this outstanding open challenge in master-slave manipulation.